Problems of the education system associated with its informatization and support tasks methods - Ashurova D. N. (Interactive science, 2016)
in this paper, the researchers analyzed various problematic issues existing in the education system. The paper discusses in detail the principles of supporting tasks methodics, the authors used in practice.
Keywords: обучение; система образования; знания; умения; навыки; training; skills; концепция обучения; методика опорных задач; system of education; knowledges; training concept; the method of support tasks